Loading web-font TeX/Math/Italic

(-5+-3x)(3+-2x)=0

Simple and best practice solution for (-5+-3x)(3+-2x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-5+-3x)(3+-2x)=0 equation:



(-5+-3x)(3+-2x)=0
We add all the numbers together, and all the variables
(-3x)(-2x)=0
We multiply parentheses ..
(+6x^2)=0
We get rid of parentheses
6x^2=0
a = 6; b = 0; c = 0;
Δ = b2-4ac
Δ = 02-4·6·0
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:
x=\frac{-b}{2a}=\frac{0}{12}=0

See similar equations:

| 10=z/3+9 | | 2x^2+6x=14 | | 16s^2-8s+1=0 | | ×-5y=17 | | 14=-12+5x-3x | | |4x-5|=2x-1 | | 2c/4+3c/2=1 | | 2n+10=—2+4n | | 5x+6x-10+x+5=180 | | 11×3p-7=6p+5-3p | | 9+2x1N=3x1N-2 | | 2x(x^2+2x-5)=0 | | -7d+d+-3d+2d=7 | | -2x+9-7x+9=27 | | 3d-2(-8+5d)=-3d-3d | | x+(-16)=-38 | | 5p5p=6p-2 | | 3+5p=6p+1-3p+6 | | —8—n=4—4n | | 1b-4+8b=21 | | -4=x5 | | 9.50n+1.25(3n+2)=68.75 | | -10x-15x-3x=8 | | -16=9x-7 | | -5x=16x-7 | | 9.50n+(1.25*3n)+2=68.75 | | 14=5+x/2 | | 244=14b+6 | | 11r-5r+2r+3r-8r=18 | | z^2+14z+28=0 | | 1+8x+9=-202x | | (h/4)^2*h=108 |

Equations solver categories